In vitro and in vivo mechanical properties of human ulnar and median nerves. Issue 9 (9th April 2013) - Ma, Zhijun; Hu, Shihao; Tan, Juay Seng; Myer, Christopher; Njus, Nina M.; Xia, Zhenhai
<x xml:space="preserve">Abstract</x> Peripheral nerves are often subjected to mechanical stretching, which in excess results in various degrees of impairment of their function. An understanding of the biomechanical behavior of peripheral nerves is important to the prevention of nerve injury during surgical manipulation. Here, in vitro mechanical properties and viscoelastic behavior of human ulnar/median nerves were measured with a tensile tester. In vivo stress and deformation of an ulnar nerve was also examined in continuity during a surgical procedure. Finite element models were developed to determine in vitro and in vivo viscoelastic parameters of the nerves. The results show that in vitro mechanical properties of fresh ulnar nerve are different from those measured in vivo. Several factors that are possibly attributed to the difference were analyzed. The in situ strain of the nerves is one of the major factors that must be considered to obtain accurate strain–stress relationship in the in vivo measurement. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2718–2725, 2013.